Writing the Holocaust : identity, testimony, representation - Waxman, Zoë (Oxford historical monographs., 2006)
Zo--euml--; Waxman examines the full history of Holocaust testimony, from the very first chroniclers confined to Nazi-enforced ghettos, to today's survivors writing as part of collective memory. Showing how dramatically the conditions and motivations for bearing witness have changed, she reveals the multiplicity of Holocaust experience and how different contexts have given rise to very different modes of remembering. - ;Arguing against the prevailing view that Holocaust survivors (encouraged by a new and flourishing culture of 'witnessing') have come forward only recently to tell their stories.